Durabilidade de pastas de cimento contendo a rede polimérica Epoxy-Etilenodiamina : avaliações em ambientes aquosos quimicamente agressivos - Santos, Danilo Oliveira (2017)
Cement slurries are used in oil wells to isolate the production area from the rock formation. An important property of these materials is their durability. Due to the interactions of the cement slurries with aggressive media in the oil wells, the durability can be threatened or lost. Cement slurries modified with polymers are promising materials candidates for cementing oil wells. Thus, it is necessary to evaluate new materials in hostile environments. In this work, new cement slurries were prepared with the Epoxy resin and the ethylenediamine hardener in two different media: distilled water and sea water. The new slurries were tested for their mechanical properties and characterized before and after interaction with the following media: production water, hydrochloric acid solution and mud acid solution. After 365 days of contact with the production water, the modified slurries showed greater chemical and mechanical resistance compared to the slurries without the polymer network (Standard slurries). Moreover, for the modified slurries after contact with the production water, a decrease of 9% in the compressive strength occurred, whereas for the slurries without the polymer network, the reduction reached 40%. Kinetic studies, chemical and thermodynamic equilibrium were carried out in the investigation of the interaction of the cement slurries with the solutions of HCl and mud acid. The results have suggested that the interactions between the modified slurries and the acid media are due to surface reactions with preservation of the hydrated compounds of the cement, causing a mass loss around 25%. For the standard slurries, the mechanism is predominantly diffusion, with structural deterioration of these slurries and mass loss of approximately 46%. Thus, the modified slurries with the polymer network Epoxy-EDA presented good characteristics to be used in the oil well procedures.